TNFR1 inhibition with a Nanobody protects against EAE development in mice - Steeland, Sophie (Sci Rep, 2017)
TNF has as detrimental role in multiple sclerosis (MS), however, anti-TNF medication is not working. Selective TNF/TNFR1 inhibition whilst sparing TNFR2 signaling reduces the pro-inflammatory effects of TNF but preserves the important neuroprotective signals via TNFR2. We previously reported the generation of a Nanobody-based selective inhibitor of human TNFR1, TROS that will be tested in experimental autoimmune encephalomyelitis (EAE). We specifically antagonized TNF/TNFR1 signaling using TROS in a murine model of MS, namely MOG(35-55)-induced EAE. Because TROS does not cross-react with mouse TNFR1, we generated mice expressing human TNFR1 in a mouse TNFR1-knockout background (hTNFR1 Tg), and we determined biodistribution of (99m)Tc-TROS and effectiveness of TROS in EAE in those mice. Biodistribution analysis demonstrated that intraperitoneally injected TROS is retained more in organs of hTNFR1 Tg mice compared to wild type mice. TROS was also detected in the cerebrospinal fluid (CSF) of hTNFR1 Tg mice. Prophylactic TROS administration significantly delayed disease onset and ameliorated its symptoms. Moreover, treatment initiated early after disease onset prevented further disease development. TROS reduced spinal cord inflammation and neuroinflammation, and preserved myelin and neurons. Collectively, our data illustrate that TNFR1 is a promising therapeutic target in MS.